Closure - Journal of Infrastructure & Facility Asset Management (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2022)
Journal of Infrastructure & Facility Asset ManagementVolume 4, Issue 1, April 2022 (e) ISSN 2656-8896 (P) ISSN 2656-890XJIFAM, Vol.3, Issue 3, December 2021A New Approach to Estimate the Potential Assets Loss due to Dam-Break Event in Indonesia Farrel Wiguna, Doddi Yudianto, Bobby Minola Ginting & Albert WicaksonoThe Effect of Addition RAP as Quality Improved for Hot Paved Mixtures Irfan Zhain, Ria Asih Aryani Soemitro & Hitapriya SuprayitnoThe Socio-economic Transformations in the Peri-urban of Bandung Metropolitan Area Yanti Budiyantini & Sheilla AlvianyThe spatiotemporal variable effects of individuals' CO2 emission in Bandung Metropolitan Areas Dimas B.E. Dharmowijoyo & Cynthia D. MaharaniManaging the Past into Future: Materiality and Discourse on Cultural LandscapeWijaya Martokusomo Wijaya Martokusumo JIFAM, Vol.3, Issue 2, August 2021Neighborhood for Adolescent Girls: The Case of Urban Dense Kampong In Yogyakarta City Center Mu’afifah & SetiawanCengklik Reservoir Tourism Development with approach Eco-WaterfrontAuliya Rohmah Ramadhani, Budi Prayitno & Wiwik SetyaningsihEarly Chinese Settlements Adaptive Reuse as History and Activity Node at Lasem Living MuseumArdelia J. Cungwin & Widjaja MartokusumoImprovement Strategy for KOTAKU program in Slum Settlements Area in SidoarjoRirin Putri Kusuma & Dian RahmawatiUrban Resilience: How to Apply in the Planning and Design Practice?Novi Maulida Ni’mah & Bakti Setiawan